Meta-MOGA: Meta-learning Multi-Objective Genetic Algorithm - Li, Tianyu; Wu, Kai; Li, Xiaobin; Teng, Xiangyi; Liu, Jing (2025 IEEE Congress on Evolutionary Computation (CEC), 2025)
In the field of single objective optimization algorithms, learned evolutionary algorithms have achieved success in obtaining better performance than human-designed strategies. However, these learnable evolutionary algorithms are only applicable to single-objective optimization and cannot be applied to multi-objective optimization problems. In this study, we parameterize the mutation and crossover operators using the multi-head self-attention and the selection operator using a lightweight multilayer perceptron. We utilize the evolution strategy to train their parameters across multiple multi-objective optimization problems, resulting in the development of the Meta-Learned Multi-Objective Genetic Algorithm (Meta-MOGA). We compare Meta-MOGA with other multi-objective evolutionary algorithms on various test problems and evaluate its performance on untrained MOPs. The results demonstrate that our Meta-MOGA exhibits potential and generalizability.